Pengaruh Model Pembelajaran VAK (Visualization, Auditory, Kinesthetic) Berbantuan Aplikasi Crossword LABS untuk Meningkatkan Pemahaman Konsep - Annisa Khaliza Damanik; Nanda Novita; Deassy Siska; Halimatus Sakdiah; Arlin Maya Sari (Universitas Hamzanwadi, 2025)
Research on the Effect of Learning Models (Visualization, Auditory, Kinesthetic) Assisted by the Crossword LABS Application to Improve Concept Understanding has been conducted. This study aims to determine the effect of the VAK learning model (Visualization, Auditory, Kinesthetic) assisted by the Crossword LABS application on students' conceptual understanding and to determine the improvement in students' conceptual understanding. The type of research used is an experiment with a research design used by researchers is a quasi-experimental design with a nonequivalent control group design. The population used is class X students of SMA which consists of 3 classes with a total of 75 people. The research sample is class X-2 students as the experimental class and class X-1 students as the control class. The average pretest result of students in the experimental class is 37.2 and the average posttest result is 77.2. Based on the Independent Samples Test, the posttest value with sig. (2-tailed) 0.004 <0.05. This means that H0 is rejected and Ha is accepted. The N-gain score for the experimental class was 64.54, which is categorized as moderate, with the interpretation of N-Gain being quite effective. Therefore, it can be concluded that the Crossword LABS application-assisted VAK (Visualization, Auditory, Kinesthetic) learning model has an impact on improving conceptual understanding.